Aditional Protocol No. 16 to The European Convention on Human Rights (the dialogue protocol) - Corona Macías, Luis Antonio (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
Throughout the history of international human rights law, regional protection systems have emerged as the most effective mechanisms for establishing common standards among countries for their protection. However, the consolidation of these standards has occurred almost exclusively through the contentious functions of regional courts (such as the European Court of Human Rights), with the consultative function of these courts being largely overlooked. Consequently, considering the success of the European Court of Human Rights and the overwhelming number of cases it receives annually, it was decided to amend the advisory procedure through Protocol No. 16 to the Convention. This amendment aims to create a new avenue for interaction between national supreme courts and the ECHR, thereby establishing a new international procedure intended to enhance the protection of human rights.